2015
DOI: 10.1371/journal.pone.0137244
|View full text |Cite
|
Sign up to set email alerts
|

Population Variation in the Life History of a Land Fish, Alticus arnoldorum, and the Effects of Predation and Density

Abstract: Life history variation can often reflect differences in age-specific mortality within populations, with the general expectation that reproduction should be shifted away from ages experiencing increased mortality. Investigators of life history in vertebrates frequently focus on the impact of predation, but there is increasing evidence that predation may have unexpected impacts on population density that in turn prompt unexpected changes in life history. There are also other reasons why density might impact life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Conducting similar experimental manipulations is likely to be impractical for blennies. However, we do know that populations of the land species A. arnoldorum on Guam vary in predation pressure and density (Morgans et al 2014), and that these populations exhibit differences in reproductive effort and growth rate in a way consistent with the notion that increases in reproductive effort (at the expense of grow rate) reflect a reduction in predation [and to some extent competition (Platt and Ord 2015)]. These data provide support for the general hypothesis in the current study that improvements in female survival may have prompted the observed changes in life history following the transition to land, with this probable change in survival potentially reflecting some form of ecological release such as a reduction in predation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Conducting similar experimental manipulations is likely to be impractical for blennies. However, we do know that populations of the land species A. arnoldorum on Guam vary in predation pressure and density (Morgans et al 2014), and that these populations exhibit differences in reproductive effort and growth rate in a way consistent with the notion that increases in reproductive effort (at the expense of grow rate) reflect a reduction in predation [and to some extent competition (Platt and Ord 2015)]. These data provide support for the general hypothesis in the current study that improvements in female survival may have prompted the observed changes in life history following the transition to land, with this probable change in survival potentially reflecting some form of ecological release such as a reduction in predation.…”
Section: Discussionmentioning
confidence: 57%
“…This might occur, for example, if the transition onto land released fish from resource competition or predation that tended to reduce the survival of younger individuals in the aquatic environment (e.g. Osenberg et al 1992;Belk 1995;Platt and Ord 2015). Marine fishes are subject to extremely high mortality during the juvenile stage (Victor 1986;Myers and Cadigan 1993), usually due to size-selective predation (Almany and Webster 2006), but also because of competition for resources (Forrester 1990), such as habitat (Shulman 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the amphibious fishes of Blenniidae, the likelihood of encountering novel predators in a terrestrial environment appears to have been circumvented through the evolution of cryptic body coloration in aquatic ancestors (i.e., blennies were already well camouflaged in their aquatic environment such that they should still be cryptic to most visual‐oriented predators on land as well; Morgans and Ord ). There is also some evidence of changes in life history that might be consistent with shifts in competition and predation, but these would reflect an ecological release from these factors following the transition to land, not vice versa (Platt and Ord ; Platt et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…We removed the right sagittal otolith via dissection of the otic capsule, following removal of the operculum. Each otolith was then washed in distilled water, air-dried, and glass-slide mounted in a thermoplastic mounting adhesive (Crystalbond 509, Aremco Inc., Valley Cottage, NY), with the transverse plane oriented parallel to the slide [60, 64]. The otolith was then filed down on one side with increasingly fine grades of wet sandpaper (from 25 to 8 μm), the plastic melted to allow the entire otolith to be inverted, and the filing processing repeated on the other side until a thin and translucent transverse section remained.…”
Section: Methodsmentioning
confidence: 99%